In situ Formed Implants, Based on PLGA and Eudragit Blends, for Novel Florfenicol Controlled Release Formulations - Karp, Federico (2021)
Drug controlled release technologies (DCRTs) represent an opportunity for designing new therapies. Main objectives are dose number optimization and secondary effects reduction to improve the level of patient/client acceptance. The present work studies DCRTs based in blended polymeric implants for single dose and long-term therapies of florfenicol (FF), a broad spectrum antibiotic. Polymers used were PLGA and Eudragit E100/S100 types. Eudragit/PLGA and FF/PLGA ratios were the main studied factors in terms of encapsulation efficiencies (EEs) and drug release profiles. In addition, morphological and physicochemical characterization were carried out. EEs were of 50-100% depending on formulation composition, and the FF releasing rate was increased or diminished when E100 or S100 were added, respectively. PLGA hydrolytic cleavage products possibly affect Eudragit solubility and matrix stability. Different mathematical models were used for better understanding and simulating release processes. Implants maintained the antimicrobial activity against Pseudomonas aeruginosa up to 12 days on agar plates. The developed DCRTs represents a suitable alternative for florfenicol long-term therapies.